The coastal streamflow flux in the Regional Arctic System Model - Hamman, Joseph; Nijssen, Bart; Roberts, Andrew; Craig, Anthony; Maslowski, Wieslaw; Osinski, Robert (American Geophysical Union, 2017)
The article of record as published may be found at http://dx.doi.org/10.1002/2016JC012323 Accepted article The coastal streamflow flux from the Arctic drainage basin is an important driver of dynamics in the coupled ice-ocean system. Comprising more than one-third of the total freshwater flux into the Arctic Ocean, streamflow is a key component of the regional and global freshwater cycle. To better represent the coupling of the streamflow flux to the ocean, we have developed and applied the RVIC streamflow routing model within the Regional Arctic System Model (RASM). The RASM is a high-resolution regional Earth System Model whose domain includes all of the Arctic drainage basin. In this paper, we introduce the RVIC streamflow routing model, detailing its application within RASM and its advancements in terms of representing high-resolution streamflow processes. We evaluate model simulated streamflow relative to in-situ observations and demonstrate a method for improving model performance using a simple optimization procedure. We also present a new, spatially and temporally consistent, high-resolution dataset of coastal freshwater fluxes for the Arctic drainage basin and surrounding areas that is based on a fully-coupled RASM simulation and intended for use in Arctic Ocean modeling applications. This dataset is evaluated relative to other coastal streamflow datasets commonly used by the ocean modeling community. We demonstrate that the RASM-simulated streamflow flux better represents the annual cycle than existing datasets, especially in ungauged areas. Finally, we assess the impact that streamflow has on the coupled ice-ocean system, finding that the presence of streamflow leads to reduced sea surface salinity, increased sea surface temperatures and decreased sea ice thickness. Department of Energy (DOE) Grant DE-FG02-07ER64460 Department of Energy (DOE) Grant DE-SC0006856 Department of Energy (DOE) DE-SC0005783 Department of Energy (DOE) DE-SC0005522 United States Department of Energy (DOE)